Contrasted spatial and long-term trends in precipitation chemistry and deposition fluxes at rural stations in France. (December 2016) - Pascaud, A.; Sauvage, S.; Coddeville, P.; Nicolas, M.; Croisé, L.; Mezdour, A.; Probst, A.
Abstract: The long-distance effect of atmospheric pollution on ecosystems has led to the conclusion of international agreements to regulate atmospheric emissions and monitor their impact. This study investigated variations in atmospheric deposition chemistry in France using data gathered from three different monitoring networks (37 stations) over the period from 1995 to 2007. Despite some methodological differences ( e.g. type of collector, frequency of sampling and analysis), converging results were found in spatial variations, seasonal patterns and temporal trends. With regard to spatial variations, the mean annual pH in particular ranged from 4.9 in the north-east to 5.8 in the south-east. This gradient was related to the concentration of NO3 − and non-sea-salt SO4 2− (maximum volume-weighted mean of 38 and 31 μeq l −1 respectively) and of acid-neutralising compounds such as non-sea-salt Ca 2+ and NH4 + . In terms of seasonal variations, winter and autumn pH were linked to lower acidity neutralisation than during the warm season. The temporal trends in atmospheric deposition varied depending on the chemical species and site location. The most significant and widespread trend was the decrease in non-sea-salt SO4 2− concentrations (significant at 65% of the stations). At the same time, many stations showed an increasing trend in annual pH (+0.3 on average for 16 stations). These two trends are probably due to the reduction in SO2 emissions that has been imposed in Europe since the 1980s. Temporal trends in inorganic N concentrations were rather moderate and not consistent with the trends reported in emission estimates. Despite the reduction in NOx emissions, NO3 − concentrations in atmospheric deposition remained mostly unchanged or even increased at three stations (+0.43 μeq l −1 yr −1 on average). In contrast NH4 + concentrations in atmospheric deposition decreased at several stations located in western and northern areas, while the estimates of NH3 emissions remained fairly stable. The decrease in non-sea-salt SO4 2− and NH4 + concentrations was mainly due to a decrease in summer values and can in part be related to a dilution process since the precipitation amount showed an increasing trend during the summer. Furthermore, increasing trends in NO3 − concentrations in the spring and, to a lesser extent, in NH4 + concentrations suggested that other atmospheric physicochemical processes should also be taken into account. Highlights: Atmospheric deposition highlighted contrasting spatial patterns in France. Inorganic compounds exhibited common trends in both wet-only and bulk deposition. nssSO4 2− concentrations primarily experienced the largest decreasing annual trend in the summer. A large number of stations showed an increasing trend in annual pH. Trends in nitrogen compounds were not linked to emission inventory changes.